2020
DOI: 10.3390/d12120456
|View full text |Cite
|
Sign up to set email alerts
|

The Coupled Influence of Thermal Physiology and Biotic Interactions on the Distribution and Density of Ant Species along an Elevational Gradient

Abstract: A fundamental tenet of biogeography is that abiotic and biotic factors interact to shape the distributions of species and the organization of communities, with interactions being more important in benign environments, and environmental filtering more important in stressful environments. This pattern is often inferred using large databases or phylogenetic signal, but physiological mechanisms underlying such patterns are rarely examined. We focused on 18 ant species at 29 sites along an extensive elevational gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…In general, species in regions with higher maximum temperatures were more heat tolerant, and species in regions with higher minimum temperatures were less cold tolerant; species in regions with higher mean temperatures showed greater tolerance to both heat and cold. Chick et al (2020) found that CT max and CT min of 18 ant species found along an elevational gradient in the Great Smoky Mountains National Park (USA) were correlated with mean annual temperature: species occurring at the warmest sites all had the highest CT max values, and species occurring at the coldest sites all had the lowest CT min values, a pattern that was consistent both among populations of the same species and among communities. Bujan et al (2020a) measured CT max and CT min for 132 ant species in 31 communities across North America (latitudinal range of 15.7 ) to assess whether these two metrics were correlated with environmental temperatures (monthly mean, maximum, and minimum).…”
Section: Abiotic and Biotic Determinants Of Ant Thermal Limitsmentioning
confidence: 85%
See 2 more Smart Citations
“…In general, species in regions with higher maximum temperatures were more heat tolerant, and species in regions with higher minimum temperatures were less cold tolerant; species in regions with higher mean temperatures showed greater tolerance to both heat and cold. Chick et al (2020) found that CT max and CT min of 18 ant species found along an elevational gradient in the Great Smoky Mountains National Park (USA) were correlated with mean annual temperature: species occurring at the warmest sites all had the highest CT max values, and species occurring at the coldest sites all had the lowest CT min values, a pattern that was consistent both among populations of the same species and among communities. Bujan et al (2020a) measured CT max and CT min for 132 ant species in 31 communities across North America (latitudinal range of 15.7 ) to assess whether these two metrics were correlated with environmental temperatures (monthly mean, maximum, and minimum).…”
Section: Abiotic and Biotic Determinants Of Ant Thermal Limitsmentioning
confidence: 85%
“…Diamond & Chick (2018b) characterised thermal tolerance breadth for 41 species from 22 genera, showing that species with narrow thermal tolerance breadth had more restricted, more equatorial ranges, suggesting they may be at greater extinction risk under climate change. Similarly, Chick et al (2020) estimated thermal tolerance breadth for 18 ant species along an elevational gradient in Great Smoky Mountains National Park (USA). They found that thermal breadth was moderately positively correlated (50%) with elevational distribution range.…”
Section: Physiological Thermal Limits Species Distribution Ranges And...mentioning
confidence: 99%
See 1 more Smart Citation
“…The proximate mechanisms underlying species distributions are poorly understood, and this is the focus of a study of ant species occurring along an elevational gradient in Great Smoky Mountains National Park in south-eastern USA [5]. Thermal tolerance appeared to be the most important constraint on the distribution and density of ant species in colder (higher elevation) environments, whereas competition was identified as a key factor in warmer (lowland) environments.…”
mentioning
confidence: 99%
“…The second paper on community ecology [8] examines the extent to which a numerically dominant ant (Formica subsericea) affects the diversity and performance of co-occurring species. As in [5], the study was conducted in the Great Smoky Mountains National Park, where F. subsericea is particularly common. There was no relationship between the abundance of F. subsericea and the total abundance of non-dominant species across the ten sites studied, and the relationship with total species richness was weak.…”
mentioning
confidence: 99%